Design and electro-optic investigations of de Vries chiral smectic liquid crystals for exhibiting broad temperature ranges of SmA* and SmC* phases and fast electro-optic switching. Issue 14 (11th March 2020) - Swaminathan, V.; Panov, V. P.; Panov, A.; Rodriguez-Lojo, D.; Stevenson, P. J.; Gorecka, E.; Vij, Jagdish K.
Abstract : Two new ferroelectric liquid crystalline compounds using 5-phenyl-pyrimidine core terminated by achiral trisiloxane chain, and chiral ( S ) alkyl chain on the opposite ends of their respective mesogens are designed with better characteristics of switching speed and broader temperature range. Abstract : In this paper, we report on the design, synthesis and characterisation of two new ferroelectric liquid crystalline compounds based on using the cores of (i) 5-phenyl-pyrimidine benzene and (ii) 5-phenyl-pyrimidine benzoate terminated by achiral trisiloxane chain, and chiral ( S ) alkyl chain on the opposite ends of their respective mesogens. These compounds exhibit broad temperature ranges of SmA* and SmC* phases, whereas the latter exists at room temperature down to 11 °C. This is one of the desirable features of the compounds for perspective applications in devices. In both compounds, the differential scanning calorimetry shows a weak first order SmA*–SmC* transition. This observation is supported by determining the critical exponent of the power law as ∼0.2 that describes the dependence of the tilt angle and the spontaneous polarization on temperature. The two compounds show excellent de Vries characteristics in terms of lower layer shrinkages in SmC*, the maximum shrinkage in both cases is ∼1.5%. Furthermore (i) the birefringence decreases with a reduction in temperature instead of an increase in SmA*, and (ii) a large field-induced birefringence is observed in SmA* close to the SmA*–SmC* transition temperature, (iii) the maximum birefringence measured is much lower than that of a typical FLC material. The characteristics of these compounds when compared to a conventional/typical ferroelectric liquid crystalline mixture show that these materials surpass in performance in terms of having a (i) wider temperature range of both SmA* and SmC* phases and (ii) higher switching speed. The layer thickness in SmA* and SmC* is measured using the techniques of (a) small-angle X ray diffraction, and the (b) optical interferometry of free standing smectic films. A comparison of the results is used to determine an exceptionally useful result of the apparent tilt angle as a function of temperature in SmA* without the need to apply the electric field across the cell.